The incel rebellion : the rise of the manosphere and the virtual war against women - Sugiura, Lisa (Emerald studies in digital crime, technology and social harms., 2021)
Emerging alongside the progression of women's rights in the twenty-first century is the development of the men's rights movement, parts of which have culminated into the contemporary 'manosphere.' Consisting of online communities that ascribe to misogynistic ideologies, which objectify, disparage, and dehumanise women, the manosphere also houses those who identify as involuntary celibate (incel). Drawing on ethnographic research and interviews, this book provides an original and timely insight into the development of the manosphere, how and why people join and self-identify as incel, the extent to which the influence and philosophy of incel and the incelsphere draws on and is penetrating mainstream culture and political discourse, and its harmful impact. The Incel Rebellion is essential reading for a broad range of practitioners and scholars across criminology, sociology, terrorism studies, gender, media and cultural studies, and politics, as well as expanding the field of cybercrime research and beyond. The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online.